2012
DOI: 10.1007/s00432-012-1325-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of neoadjuvant systemic therapy for locally advanced breast cancer in routine clinical practice

Abstract: PurposeThe aim of this study is to evaluate the long-term outcome of patients with locally advanced breast cancer treated with neoadjuvant systemic chemotherapy (NST) in routine clinical practice.MethodsFour hundred and nine patients were identified between January 1999 and December 2011. All patients received NST followed by surgery, adjuvant treatments and radiotherapy, as appropriate.ResultsAt Kaplan–Meier analysis, patients with surgical stage III disease were more likely to develop distant metastasis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
(66 reference statements)
4
16
0
Order By: Relevance
“…Luminal B/HER2+ molecular subclass was associated with a better outcome, as reported for luminal A, luminal B/HER2-negative and luminal B/HER2+ tumors in other series (Goldhirsch et al 2011; Angelucci et al 2012; Houssami et al 2012; Tran and Bedard 2011). Pathological stage 0–I was also predictive of better outcome in our cohort of patients, in line with data showing that among patients with residual disease, a higher tumor burden at surgery is predictive of a worst outcome (Fisher et al 1998; Angelucci et al 2012; Cance et al 2002; Carey et al 2005). …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Luminal B/HER2+ molecular subclass was associated with a better outcome, as reported for luminal A, luminal B/HER2-negative and luminal B/HER2+ tumors in other series (Goldhirsch et al 2011; Angelucci et al 2012; Houssami et al 2012; Tran and Bedard 2011). Pathological stage 0–I was also predictive of better outcome in our cohort of patients, in line with data showing that among patients with residual disease, a higher tumor burden at surgery is predictive of a worst outcome (Fisher et al 1998; Angelucci et al 2012; Cance et al 2002; Carey et al 2005). …”
Section: Discussionsupporting
confidence: 73%
“…However, this predictive potential of pCR has been recently questioned by various authors, particularly in relation to the molecular subclasses of breast cancer (Goldhirsch et al 2011). In fact, patients with luminal A [steroid hormone receptors positive, HER2 negative, low proliferative activity] breast cancer usually show a very low rate of pCR, but their prognosis remains good even when no pCR is achieved (Angelucci et al 2012; Colleoni et al 2009; Huober et al 2010; Precht et al 2010; Straver et al 2010; Kim et al 2010; von Minckwitz et al 2012). It has been recently reported that pCR is not predictive of survival also in luminal B/HER2+ tumors (steroid hormone receptors positive, HER2+) even when neoadjuvant trastuzumab is administered (von Minckwitz et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For each cohort, 10 multiple imputed data sets were created and used for the analyses. Two studies did not provide data regarding menopausal status, 2 did not provide data regarding preoperative N classification, and 1 study did not provide data regarding pCR . To assign values for these missing data, we performed multiple imputations using all relevant potential predictive factors from the pooled data set using the same method.…”
Section: Methodsmentioning
confidence: 99%
“…This observation is comparable with that of Henry M. Kuerer et al who demonstrated that neo-adjuvant chemotherapy has the capacity to completely clear the breast and axillary lymph nodes of invasive tumours before surgery. 10 Hung WK et al, Stuart A McIntosh et al Poole GV et al also showed the same response in their studies. [23][24][25] All the 16 LABC patients who had recurrence in the present study received full course of NACT treatment and achieved complete pathological response after it.…”
Section: Discussionmentioning
confidence: 54%
“…[7][8][9] The down-staging of the primary tumour and the increase in breast conservation rates seems to be the clinical benefit of NACT. 10 Neoadjuvant chemotherapy also has the capacity to completely clear the breast and axillary lymphnodes of invasive tumour before surgery.…”
Section: Introductionmentioning
confidence: 99%